PENGURAIAN SAMPAH ORGANIK DI MUARA KALI KRESEK UNTUK PARAMETER TOTAL NITROGEN, PHOSPHAT, MINYAK DAN LEMAK - Hendrawan, Diana; Widyatmoko, H.; Efria, Anggi (Jurnal Teknologi Lingkungan Universitas Trisakti, 2007)
Analysis of Applying the Environment Management System ISO 14001 2004 The objective of this research was to identify physical and chemical characteristics in Kresek estuary. Total Nitrogen, Phosphate and Oil Fat concentration were the pollutants distributed in every segment based on depth and distance as well as estimate the amount of decomposition from pollutant concentration. Sampling was conducted on early April 2008 through 3 observation segments. The result of measurement in the depth of 1 m from water surface is the temperature around 26–30 °C; ph water 6,84–7,14; speed 0,3–1,8; TDS 231–11040 mg/l; TSS 2,03–11,25 mg/l; muddy 3,5–45 mg/l; DO 5,7–6,7 mg/l; total nitrogen 6,69–8,97 mg/l; phosphate 0,154–0,395 mg/l. The result of measurement in the depth of 1,5 m from water surface is the temperature around 26–30°C; ph water 6,9–7,19; speed 0,1–0,13; TDS 236–11542 mg/l; TSS 8,5–13,25 mg/l; muddy 3,9–59 mg/l; DO 5,7–6,9 mg/l; total nitrogen 7,62–9,71 g/l; phosphate 0,235–0,499 mg/l. Further, the result of analysis was compared by standard quality based on the Decree of The Governor of DKI Jakarta No. 582/1995 Group C. The result of analysis in the depth of 1 m and 1,5 m exceeding quality standard of The Governor’s Decree No. 582/1995 Group C was TDS and total nitrogen. The result of nitrogen organic decomposition calculation influenced by oxygen content in water with using mass scale seen from total nitrogen concentration namely organic coming inside river in the depth of 1 m was in amount of 0,223 kg/s and organic coming inside the river in the depth was in amount of 0,738 kg/s. Abstract in Bahasa Indonesia: Analysis of Applying the Environment Management System ISO 14001 2004 Muara Kresek merupakan muara kali Sunter yang mempunyai kedalaman 6 – 10 m. Muara Kresek berada diwilayah kelurahan Lagoa, Jakarta Utara. Tujuan penelitian adalah mengetahui konsentrasi Total Nitrogen, Phosphat, dan Minyak Lemak di Muara kresek, mengetahui distribusi pencemar pada tiap-tiap segmen berdasarkan kedalaman dan jarak dan menghitung besar penguraian konsentrasi pencemar. Pengambilan sampel dilakukan pada awal bulan April 2008, dari 3 segmen pengamatan. Hasil pengukuran pada kedalaman 1 m dari permukaan air yaitu suhu berkisar antara 26-30 oC; pH air 6,84-7,14; keceapatan 0,3-1,8; TDS 231-11040 mg/l; TSS 2,03-11,25 mg/l; Kekeruhan 3,5-45 mg/l; DO 5,7-6,7 mg/l;total nitrogen 6,69-8,97 mg/l; phosphat 0,154-0,395 mg/l. Hasil pengukuran pada kedalaman 1,5 m dari permukaan yaitu suhu berkisar antara 26-30 oC; pH air 6,9-7,19; keceapatan 0,1-0,3; TDS 236-11542 mg/l; TSS 8,5-13,25 mg/l; Kekeruhan 3,9-59 mg/l; DO 5,7-6,9 mg/l; total nitrogen 7,62-9,71g/l; phosphat 0,235-0,499 mg/l. Hasil analisis kemudian dibandingkan oleh baku mutu SK Gubernur DKI Jakarta No. 582/1995 Golongan C. Hasil analisis pada kedalaman 1m dan 1,5 m yang melebihi baku mutu SK Gubernur DKI Jakarta No.582/1995 Golongan C adalah TDS dan total nitrogen. Hasil perhitungan penguraian organik nitrogen yang dipengaruhi oleh kandungan oksigen dalam air dengan menggunakan perhitungan neraca massa yang dilihat dari konsentrasi total nitrogen yaitu organik yang masuk ke dalam sungai pada kedalaman 1 m sebesar 0,223 kg/det.dan organik yang masuk ke sungai pada kedalaman 1,5 m sebesar 0,738 kg/det.